2022
DOI: 10.30574/gjeta.2022.11.2.0083
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of ethical issues and the effect of artificial intelligence on the cryptocurrency market

Abstract: The world has gradually embraced Cryptocurrency at various levels of capacity and it is not governed or regulated by any Control system. It has over time been used by participants as a means to invest despite the volatility of the market. Though Government does not have the means to outright stop the virtual marketing deals of Cryptocurrency, recently Nigerian government called for deposit money banks to close all corresponding accounts which are perceived to be involved in Cryptocurrency trading. The Crypto m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Research has shown that some of the common features of fraudulent schemes are mouth-watering returns and no negative impacts 1 , 29 . Findings suggest that increased regulatory supervision with tight requirements for compulsory reporting of their activities will help to identify such schemes 30 .…”
Section: Related Workmentioning
confidence: 99%
“…Research has shown that some of the common features of fraudulent schemes are mouth-watering returns and no negative impacts 1 , 29 . Findings suggest that increased regulatory supervision with tight requirements for compulsory reporting of their activities will help to identify such schemes 30 .…”
Section: Related Workmentioning
confidence: 99%
“…These technological innovations have enabled faster execution of trades, increased market transparency, and facilitated the development of sophisticated trading strategies that respond to market signals and trends (Mikhaylov, 2020). However, they have also introduced new challenges related to market manipulation and cybersecurity (Ogunyolu & Adebayo, 2022).…”
Section: Sonal Sahumentioning
confidence: 99%